Analysis and Design of Water Supply System for Al Burj Village - Badran, Hadeel; Abdeen, Hiba; Al-Slameh, Janet (جامعة بوليتكنك فلسطين - مباني, 2008)
Al Burj village faces great problems in water supply and water services due to population growth, Hence , no water distribution network servicing the village , and the people depend mainly on water tanking and constructed cisterns for water supply , in view of this bad condition, the need for water supply scheme that will supply the entire area of Al Burj village with water requirements become pressing, and subsequently this work was conducted to study and evaluate the present situation and design a new water distribution system for Al burj village. The present study considered the annual population growth and their water demand for the coming 25 years that will be the design period, along . the hydraulic calculation needed for the design of the main and sub main pipelines is carried out using water software ( EPANET). A complete design for water distribution network for Al Burj village is ready along with bill of quantities , cost estimate , and the suggested phases of construction
no of pages 57, 22131 , مباني 16/2008 , in the store
Keywords: Water Supply Systems